HUBUNGAN CARA BELAJAR DENGAN PRESTASI BELAJAR - Yeni Yusmalia; Sumadi Sumadi; Yarmaidi Yarmaidi (JPG (Jurnal Penelitian Geografi), 2013)
The aim of this research was to find out the correlation between learning strategy and learning achievement of geography subject to XI social class students at SMA Perintis I Bandar Lampung at the year of 2011/2012. The method used in the research was correlation method. The population in this research were XI social class students who were divided into 5 classes which were 174 students. The samples taken for the research were about 35% of the total population which were 60 students using proportional random sampling technique. The data collecting technique used were questionnaire, test, and documentation, while the data analysis used was product moment correlation and to test the hypothesis, the researcher used SPSS program. This result of the research showed that ( 1 ) There was a strong and significant positive correlation between learning strategy and learning achievement of geography subject to XI social class students at SMA Perintis 1 Bandar Lampung with the correlation coefficient was 0.849. ( 2 ) There was a strong and significant correlation of reading the lesson at home and the correlation coefficient was 0.612. ( 3 ) There was a strong and significant correlation of making notes with the correlation coefficient was 0.675. ( 4 ) There was a strong and significant correlation of reviewing the lesson at home with correlation coefficient was 0.588. ( 5 ) There was a strong and significant correlation of doing the exercise at home with the correlation coefficient was 0.521. Keywords: learning strategy (making schedule, reading the lesson at home, making notes, reviewing the lesson at home, and doing the exercise at home) and learning achievement